Analyze semantic of object-oriented model using RiTa.WordNet - Ali, Noraida; Ibrahim, Noor Syakirah; Mohd Sani, Nor Fazlida; Mohamad Noor, Noor Maizura (Journal of Computing Press, 2011)
The importance of modeling is obvious with its use to predict cost and time requirement especially in completing a system. However, there is no equivalent standard for evaluating the quality of conceptual models. Thomasson has also shown the difficulties in designing the appropriate UML class diagram such as naming the notation element. The UML class diagram designed by students always neglects the quality in modeling such as consistency and accuracy. This study proposes the use of WordNet in order to achieve the quality in modeling. RiTa.WordNet will be used as a tool to extract synsets from WordNet. The use of RiTa.WordNet shows that synonyms extracted can be used to match the UML class name designed by students. This application will be used to increase the accuracy of object-oriented model.